Subphenotypic features of patients with sepsis and ARDS: a multicenter cohort study - Li, Nan; Fang, DeYu; Ge, Feng; Zhang, Lin; Liu, Ying; Jin, Hongxu; Shen, Hao; Xie, Keliang; Gao, Yan (Frontiers in Medicine, 2024)
Patients with sepsis are often comorbid with Acute Respiratory Distress Syndrome (ARDS), and the phenotypic characteristics of pulmonary and non-pulmonary infections leading to ARDS are still unclear.The aim of this study was to compare the phenotypic characteristics of ARDS resulting from pulmonary infections and other non-site infections and better guidance for clinical treatment.Methods:We conducted a multicenter cohorts analysis using data from the Tianjin Medical University General Hospital, Medical Information Mart for Intensive Care IV (MIMIC IV) and the electronic Intensive Care Unit (eICU) databases. The study population consisted of adult patients diagnosed with sepsis and ARDS. The primary objectives were to compare the characteristics and outcomes of patients with pulmonary infection and non-pulmonary infection induced ARDS by Wilcoxon, Kaplan-Meier curve, correlation analysis, propensity matching score and other methods.Results: Patients with ARDS by pulmonary infection may be more likely to have a history of chronic obstructive pulmonary disease, and abdominal infection was more likely to induced to ARDS in sepsis patients with non-pulmonary infection. Pulmonary infections caused by Klebsiella pneumoniae and Acinetobacter baumannii were more likely to induced ARDS. The oxygenation index and prognosis of ARDS patients induced by pulmonary infection were worse than those caused by other infections, with lower PaO2, PaO2/FiO2, and ROX index, longer hospital stay, more ARDS patients with pulmonary infection were given mechanical ventilation therapy, higher mortality, higher APACHE II, SOFA, SAPS II. The further correlation analysis showed that the prognostic scores of ARDS patients were negatively correlated with PaO2/FiO2 and ROX index. The above results were confirmed to varying degrees by propensity matching scores, external cohort validation and other methods.Conclusions: Pulmonary infection induces worse prognosis of ARDS than other site infections in patients with sepsis and ARDS. These patients require heightened vigilance, early intervention, and possibly more aggressive 3 management strategies.